Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x\cdot\dfrac{3}{7}-x\cdot\dfrac{1}{2}=\dfrac{3}{5}\)
\(x\left(\dfrac{3}{7}-\dfrac{1}{2}\right)=\dfrac{3}{5}\)
\(x\cdot\dfrac{-1}{14}=\dfrac{3}{5}\)
\(x=\dfrac{3}{5}:\dfrac{-1}{14}\)
\(x=\dfrac{-42}{5}\)
x - 7.84 = 64% x (2,8 + 3,7)
<=> x - 7.84 = 0,64 x 6.5
<=> x - 7,84 = 4,16
<=> x = 4,16 + 7,84 = 12
(x + \(\frac{1}{4}\) ) : 0,01 - (0,75x4) = 60
<=> (x + \(\frac{1}{4}\) ) x 100 - 3 =60
<=> 100x + 25 - 3 =60
<=> 100x = 38
<=> x = \(\frac{19}{50}\)
a, x - 7,84 = 64% x ( 2,8 + 3,7 )
x - 7,84 = 64% x 6,5
x - 7,84 = 41,6
x = 41,6 + 7,84
x = 49,44
b, ( x + 1/4 ) : 0,01 - ( 0,75 x 4 ) = 60
( x + 0,25 ) : 0,01 - 3 = 60
( x + 0,25 ) : 0,01 = 60 + 3
( x + 0,25 ) : 0,01 = 63
x + 0,25 = 63 x 0,01
x + 0,25 = 0,63
x = 0,63 - 0,25
x = 0,38
128 x X - 12 x X - 16 x X = 5 208 000
X x ( 128 - 12 - 16 ) = 5 208 000
X x 100 = 5 208 000
X = 5 208 000 : 100 = 52 080
Câu còn lại tự làm nhé !
\(x:\dfrac{1}{2}+x:\dfrac{1}{4}+x:\dfrac{1}{6}+...+x:\dfrac{1}{20}=50\\ x\times2+x\times4+x\times6+...+x\times20=50\\ x\times\left(2+4+6+...+20\right)=50\)
Ta có
\(2+4+6+...+20\\ =\left(2+20\right)+\left(4+18\right)+\left(6+16\right)+\left(8+14\right)+\left(10+12\right)\\ =22\times5=110\)
Do đó:
\(x\times110=50\\ x=\dfrac{50}{110}=\dfrac{5}{11}\)